Pembangunan Indeks Kinerja Industri - Setiawati, Dewi; Nachrowi, Nachrowi D. (Jurnal Ekonomi dan Pembangunan Indonesia, 2012)
This research develops Industrial Performance Index and shows annual performance index among industries through all and each indicator from 2004 to 2007. There are three criteria and 19 indicators, (1) output (value added, wage, firm), (2) production factor (labor, capital, and technological progress), (3) production cost (labor and capital productivity, material and energy efficiency). The result shows the best performance industry, (1) in 2007 is transportation industry excluded four or more wheel vehicle, (2) in 2006 is recycling industry, (3) in 2005 is machinery and office equipment industry, (4) in 2004 is food and beverage industry.